Taxonomic study on selected species of stingless bee (hymenoptera: apidae: meliponini) in Peninsular Malaysia - Siti Fatimah Samsudin,; Mohd Razif Mamat,; Izfa Riza Hazmi, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
A total of 19 species of stingless bee (Apidae: Meliponini) from eight genera were examined and revised, based on 145 specimens from the collection of Malaysian Agricultural Research and Development Institute (MARDI), Malaysian Genome Institute (MGI) and a sampling done in several stingless bee farms in Peninsular Malaysia. This study aims to revise a taxonomic character and provide a redescription of stingless bee based on morphological characters and morphometric measurements of 24 parameters, in order to prepare a dichotomous key to the genus and species in Peninsular Malaysia. The genera and species identification of stingless bee were based on morphological characters and coloration such as the structure and color of antenna, head, thorax, wing, leg and abdomen. Finding of the research shows that, Geniotrigona appeared as the largest genus in term of size and thus supported by the previous report. It was represented by two species namely Geniotrigona thoracica and Homotrigona fimbriata with mean body length 8.44 and 8.24 mm, respectively. Tetragonula fuscobalteata appeared as the smallest species of stingless bee with an average of body length 3.26mm. Lepidotrigona can be differentiated from other genera of stingless bees by having a yellowish scale-like structure on a mesoscutum while Tetragonula can be categorized by having a hairband on a mesoscutum. This hairband character is peculiar for Tetragonula while their species differentiation can be made whether it is obviously seen or not. Tetragonula was recorded as the most abundant genus with highest species richness accordingly to the previous literature, and represented here by eight described species. Each recorded species of stingless bee were successfully distinguished by distinct morphological characters and coloration possess by the species itself. Thus, it is hope that this study would be very useful as a guideline and reference for further studies of stingless bee in future.